Case report: mRNA-1273 COVID-19 vaccine-associated myopericarditis: Successful treatment and re-exposure with colchicine - Valore, Luca; Junker, Till; Heilmann, Eva; Zuern, Christine S.; Streif, Matthias; Drexler, Beatrice; Arranto, Christian; Halter, Jörg P.; Berger, Christoph T. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Vaccine-induced myopericarditis is a rare complication of mRNA vaccines against SARS-CoV2. Case presentation: We report a case of an acute myopericarditis in a recipient of allogeneic hematopoietic cells following the first dose of the mRNA-1273 vaccine and the successful administration of a second and third dose while on prophylactic treatment with colchicine to successfully complete the vaccination. Conclusions: Treatment and prevention of a mRNA-vaccine induced myopericarditis represent a clinical challenge. Use of colchicine is feasible and safe in order to manage this rare but severe complication and allow re-exposition to vaccine.